VARIASI PENGGUNAAN REKONTRUSI ALGORITMA FBP, iDose4 DAN ITERATIVE MODEL RECONTRUCTION (IMR) TERHADAP KUALITAS CITRA MCST THORAK LOW DOSE UNTUK MENDETEKSI NODUL PARU - Anikmah, Siti; Kartikasari, Yeti; Kurniawati, Ary (Perhimpunan Radiografer Indonesia (PARI), 2020)
Background: Pulmonary nodules are often found accidentally when thorax imaging is done. The size and rate of nodule growth are the most important predictors of imaging for malignancy. When the low dose protocol applied to the thorax MSCT will affect image quality, such as increased noise and decreased spatial resolution, so that the detection of nodules becomes less accurate. For noise limitation the reconstruction of the FBP, iDose4 and IMR algorithm is used. The purpose of this literature study is to evaluate variations in the FBP, iDose4 and IMR algorithm in improving image quality. Methods: This method is a qualitative research with a descriptive approach using comprehensive literatures studies Results: The result show that noise reduction is highest at IMR and lowest at FBP. The highest number of detected nodules on IMR especially for solid nodules < 4 mm and the lowest on FBP. Pathological findings with the best quality on IMR and quality are limited to FBP. Visibility of normal and abnormal findings, iDose4 is better than IMR and FBP especially for reticular patterns. Effective doses are reduced by 44 % to 59 % based on this literature study. In clinical practice, IMR shows the potential for pathological recovery at low dose level and IMR can improved measured image quality based on noise, high contrast spatial resolution and low contrast detectability. Conclusion: So IMR is the most effective algorithm applied for scanning low dose MSCT thorax for detection of pulmonary nodules.